2020
DOI: 10.1111/cen.14268
|View full text |Cite
|
Sign up to set email alerts
|

Presentation, disease progression and outcomes of adrenal gland metastases

Abstract: Objective: Data on the presentations and outcomes of patients with adrenal gland metastases are limited. Our objectives were to characterize the prevalence of adrenal metastases subtypes and investigate how varying clinical presentations affect disease progression, development of primary adrenal insufficiency (PAI) and mortality. Design: Single institution tertiary centre, retrospective cohort study from 1997 to 2020. Patients and Measurements: Adult patients with adrenal metastases. Clinical, radiologic and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 17 publications
(52 reference statements)
0
14
0
2
Order By: Relevance
“…Males and older age groups were more commonly affected, which is consistent with the epidemiology of the underlying primary malignancies and the generally increased prevalence of AI in the older population [ 21 ]. This is in contrast to the proportion of AI patients diagnosed in a recent case series by Mao et al, who identified that, among patients with bilateral metastatic disease, 12.4% of patients had primary AI [ 3 ] and to the estimated prevalence of 3–8% in a recent systematic review and meta-analysis [ 4 ]. The relative rarity of an AI diagnosis in this study may reflect lower levels of diagnosis or recording of this comorbidity in hospitalised patients.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Males and older age groups were more commonly affected, which is consistent with the epidemiology of the underlying primary malignancies and the generally increased prevalence of AI in the older population [ 21 ]. This is in contrast to the proportion of AI patients diagnosed in a recent case series by Mao et al, who identified that, among patients with bilateral metastatic disease, 12.4% of patients had primary AI [ 3 ] and to the estimated prevalence of 3–8% in a recent systematic review and meta-analysis [ 4 ]. The relative rarity of an AI diagnosis in this study may reflect lower levels of diagnosis or recording of this comorbidity in hospitalised patients.…”
Section: Discussionmentioning
confidence: 60%
“…The reasons for the observed 74.8% increase in admission rates associated with a metastatic adrenal malignancy, which has not been documented elsewhere, could not be determined in this analysis. However, it is likely that, in the absence of a substantial increase in diagnoses for relevant primary malignancies during this time, the greater use of imaging, both for unrelated symptoms, which was the source of 36.3% of such diagnoses in one recent case series [ 3 ]; and staging and follow-up, which characterises the modern management of cancer and was responsible for 58.5% of diagnoses in the same series, [ 3 ] may have contributed to an increase in identification of adrenal metastases. By comparison, there were fewer admissions with a primary adrenal malignancy, which showed no clear trend over the same time frame, despite the well documented increase in incidental diagnoses of (mostly benign) adrenal tumours, as a consequence of the increase in imaging for symptoms that are unrelated to adrenal disorders [ 1 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Adrenal metastasis of genitourinary primary tumors has been demonstrated to have the highest prevalence of bilateral disease. 19 In our case, the patient had bilateral adrenal metastasis from an extragonadal germ-cell tumor; hence, locating the primary tumor was challenging.…”
Section: Discussionmentioning
confidence: 86%